Analysis of the Realization of Operational Costs for Overburden Stripping and Coal Getting - Maya Matofani; Edwin Harsiga; Aisyah Mey Ardiansyah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Mining activities require mechanical equipment and costs to support production targets. Operational costs greatly affect the company's income, so it is necessary to analyze operational costs. This study analyzes the realization of operational costs to determine the causes of losses experienced by the company. The analysis process is carried out by estimating coal getting production to find out the number of tools used, namely 1 unit of digging equipment and 6 units of conveyance equipment with operational costs (fuel, oil usage, filter usage, labor wages, spare parts, grease usage, tire usage) , and equipment rental). The estimated operational costs incurred for the production of coal getting amounted to IDR 762,938,772 while the realization was IDR 302,819,845 using 1 unit of digging equipment and 5 units of transportation equipment. Estimated operational costs for stripping overburden amounted to Rp. 2,728,246,056 using 2 units of digging equipment and 12 units of hauling equipment, while the realization was Rp. 1,327,850,880 using 2 units of digging equipment and 15 units of hauling equipment. Production realization in April 2019 overburden and coal getting stripping was not achieved, this was due to the large duration of rain and slippery time. The percentage of rain duration reaches 6 percent and slippery time reaches 27 percent. The total operational costs incurred for the production of coal getting amounted to IDR 1,630,670,724.50 with a coal price of IDR 450,000 / ton and actual production of 1,106.88 tons so that the revenue from coal sales in April 2019 was IDR 498,096,000. This resulted in the company experiencing a loss of IDR 1,132,574,725. The factors that caused the company to suffer losses were low production due to the many durations of slippery rain, the operational costs incurred were greater than the income from coal sales and the number of tools that stood by reached 24 percent.